The effect of cottonseed meal and soybean oilmeal fed separately and together upon the digestibility of a ration fed to lambs. - Richardson, D. (Kansas Agricultural Experiment Station, 2012)
There is a variation in the digestibility of protein in the various concentrates fed to livestock. It has been shown that the digestibility of nutrients in a ration with a mixture of protein concentrates is closely related to the proportion of the various protein sources in the ration. However, opinions differ on the effect of single and mixed proteins upon the digestibility of protein and other nutrients in the ration of cattle and sheep. This preliminary study was to evaluate further the nutritive value of single and mixed protein concentrates in the lambs' ration.
Keywords: Sheep; Cottonseed meal; Soybean oilmeal; Digestibility